2018
DOI: 10.3390/forecast1010011
|View full text |Cite
|
Sign up to set email alerts
|

Oil Market Efficiency under a Machine Learning Perspective

Abstract: Forecasting commodities and especially oil prices have attracted significant research interest, often concluding that oil prices are not easy to forecast and implying an efficient market. In this paper, we revisit the efficient market hypothesis of the oil market, attempting to forecast the West Texas Intermediate oil prices under a machine learning framework. In doing so, we compile a dataset of 38 potential explanatory variables that are often used in the relevant literature. Next, through a selection proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Today, oil prices still fluctuate greatly due to uncertain conditions and events. Athanasia et al (2019) provided evidence that points to the rejection of even a weak form of efficiency in the crude oil market, implying that a ceiling exists in predicting oil prices [3]. Therefore, it is necessary to surmount this ceiling in order to reduce crude oil investment risks by finding other auxiliary methods.…”
Section: Introductionmentioning
confidence: 99%
“…Today, oil prices still fluctuate greatly due to uncertain conditions and events. Athanasia et al (2019) provided evidence that points to the rejection of even a weak form of efficiency in the crude oil market, implying that a ceiling exists in predicting oil prices [3]. Therefore, it is necessary to surmount this ceiling in order to reduce crude oil investment risks by finding other auxiliary methods.…”
Section: Introductionmentioning
confidence: 99%
“…value from trading data X(i), and K(X(i), X) represents the kernel function. As Dimitriadou et al [13] found that the SVM model combined with the non-linear Radial Basis Function (RBF) kernel exhibits better performances than any other kernels (e.g., linear, sigmoid), we use Gaussian Radial Basis Function…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…We do not use log returns for the monetary aggregates because we would be testing for money In brief, the cross validation is performed to avoid overfitting of our forecasting methodology to the training dataset. The optimal parameters of our forecasting methodology are identified in a coarse-to-fine grid search to avoid exhaustive search, which is computationally enormous to handle [20]. The SVM methodology finds the optimal linear classificator by maximizing the distance of the marginal data points between the two classes; when the problem is not linearly separable, the kernelization of the system (the projection of the data space into a higher space using a kernel function) allow us to search for non-linear classifiers.…”
Section: The Datamentioning
confidence: 99%